Acoustic characterization of tonal and broadband backup alarms in laboratory and field conditions. (June 2020) - Robin, Olivier; Krpic, Tamara; Nélisse, Hugues; Berry, Alain
Abstract: This paper reports results of laboratory and field tests of a tonal and a broadband backup alarms. One-, two- and three-dimensional sound pressure measurements were first conducted in a hemi-anechoic room and in a reverberant room. For the hemi-anechoic room condition, the additional effect of an absorptive or reflective ground condition was studied, as well as diffraction effects that can arise when an alarm is mounted on a rigid volume (such as a vehicle). The two alarms were then tested in field conditions. They were mounted on a forklift that was operated in a straight and reverberant corridor. One-dimensional sound pressure level measurements were made along the corridor's length with the forklift in still and moving conditions. In contrast to the tonal backup alarm, the broadband alarm shows to be overall less sensitive to ground, diffraction and room effects.